Polyvinyl chloride electrostatic film adhesive tape

Polyvinyl chloride electrostatic film tape prepared using specific materials and processes solves the problems of difficult peeling and poor antistatic effect of traditional tapes, and realizes a tape that is easy to peel and has good antistatic effect, suitable for fixing and insulating electronic components.

CN119391319AInactive Publication Date: 2025-02-07SUZHOU HENGRUI ELECTRONIC MATERIALS CO
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411748567.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional PVC tapes are difficult to peel off and have poor antistatic properties, affecting ease of use and the safety of electronic components, and also have poor storage stability.

Method used

Polyvinyl chloride electrostatic film tape is prepared by using materials such as polyvinyl chloride, perchlorate resin, nano-grade fly ash, alkylamide phosphate betaine, hydroxysulfonyl betaine, carbon fiber, aluminum dihydrogen phosphate, lithium naphthenate, and triallyl isocyanurate through specific mixing, extrusion, drying, melt extrusion, corona treatment, and pelletizing processes.

Benefits of technology

It improves the peel strength and antistatic properties of the tape, meeting the high requirements of modern industry for material performance, and is suitable for applications requiring high antistatic properties and strong adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391319A_ABST
    Figure CN119391319A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of insulating adhesive tapes for electricians, and discloses a polyvinyl chloride electrostatic film adhesive tape which comprises the following raw materials in percentage by weight: 40-45% of polyvinyl chloride; 11%-14% of perchloro-ethylene resin; 12%-16% of nano-scale fly ash; 2%-5% of alkyl amide phosphate betaine; 4%-7% of hydroxy sulfopropyl betaine; 5%-7% of carbon fibers; 4%-8% of aluminum dihydrogen phosphate; 3%-6% of lithium naphthenate; the preparation method comprises the following steps: weighing the raw materials, uniformly mixing, carrying out extrusion granulation, carrying out drying, melt extrusion, calendaring and membrane corona treatment on the granules, carrying out surface coating and printing treatment on the membrane subjected to corona treatment, and carrying out drying, melt extrusion, calendaring and membrane corona treatment on the membrane subjected to surface coating and printing treatment. The comprehensive performance of the adhesive tape can be improved by selecting the raw materials and adjusting the specific gravity range, and the antistatic performance and the peel strength of the adhesive tape can be improved by selecting the types and proportions of the perchloro-ethylene resin, the nano-scale fly ash, the carbon fibers and the betaine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrical insulating tapes, in particular to a polyvinyl chloride electrostatic film tape. Background Art

[0002] Traditional polyvinyl chloride (PVC) tape has a wide range of applications in many fields, such as wire winding, insulation and fixation of electronic parts, etc. However, this material has some obvious defects. First, PVC tape is often difficult to peel off, which not only affects the convenience of use, but also may cause damage to the surface to which it is adhered. Secondly, the antistatic effect of PVC tape is not good, which is particularly problematic in the electronics industry because static electricity may damage sensitive electronic components. In addition, the storage stability of PVC tape is poor, and the insulation, heat resistance and antistatic properties are poor, which limits its application in electrical applications. In the packaging process of electronic products, although the existing antistatic tapes are widely used, they still have problems such as unsatisfactory antistatic performance, difficulty in tearing off, and environmental protection. Therefore, the development of a PVC electrostatic film adhesive that is easy to peel off and has good antistatic effect has become an important direction of technological development. This new material needs to overcome the shortcomings of traditional PVC tape and provide more superior insulation, heat resistance and antistatic properties to meet the higher requirements of modern industry for material properties. Summary of the invention

[0003] 1. Technical issues to be solved

[0004] In view of the deficiencies in the prior art, the present invention provides a polyvinyl chloride electrostatic film tape, which has the advantages of easy tape peeling and good antistatic effect, and solves the problems of difficult tape peeling and poor antistatic effect of traditional tape.

[0005] (II) Technical solution

[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a polyvinyl chloride electrostatic film tape, wherein the raw materials of the tape and their specific gravity range are: polyvinyl chloride 40% to 45%; perchloroethylene resin 11% to 14%; nano-level fly ash 12% to 16%; alkylamide phosphate betaine 2% to 5%; hydroxysulfonpropyl betaine 4% to 7%; carbon fiber 5% to 7%; aluminum dihydrogen phosphate 4% to 8%; lithium cyclohexaneate 3% to 6%; triallyl isocyanurate 1.52% to 1.94%.

[0007] Preferably, the raw materials of the adhesive tape and their specific gravity are: 40% polyvinyl chloride; 14% perchloroethylene resin; 12% nano-level fly ash; 3% alkylamide phosphate betaine; 5% hydroxysulfonpropyl betaine; 6% carbon fiber; 7% dihydrogen aluminum phosphate; 5% lithium cyclohexaneate; and 1.60% triallyl isocyanurate.

[0008] Preferably, the raw materials of the adhesive tape and their specific gravity are: 42% polyvinyl chloride; 13% perchloroethylene resin; 12% nano-level fly ash; 2.4% alkylamide phosphate betaine; 5% hydroxysulfonpropyl betaine; 5.7% carbon fiber; 4.8% aluminum dihydrogen phosphate; 5.2% lithium cyclohexane acid; and 1.52% triallyl isocyanurate.

[0009] Preferably, the raw materials of the adhesive tape and their specific gravity are: 44% polyvinyl chloride; 14% perchloroethylene resin; 13% nano-level fly ash; 2.5% alkylamide phosphate betaine; 7% hydroxysulfonpropyl betaine; 6% carbon fiber; 8% dihydrogen aluminum phosphate; 6% lithium cyclohexaneate; and 1.94% triallyl isocyanurate.

[0010] Preferably, a polyvinyl chloride electrostatic film tape comprises the following steps:

[0011] Step 1, raw material preparation: weigh the raw materials in the formula ratio, including polyvinyl chloride, perchlorethylene resin, nano-scale fly ash, alkylamide phosphate betaine, hydroxysulfonpropyl betaine, carbon fiber, aluminum dihydrogen phosphate, lithium naphthenate and triallyl isocyanurate;

[0012] Step 2, mixing process: adding the weighed raw materials into a high-speed mixer and mixing;

[0013] Step 3: Extrusion granulation: feeding the uniformly mixed raw materials into a twin-screw extruder for extrusion granulation;

[0014] Step 4: Drying: The extruded particles are placed in an oven for drying;

[0015] Step 5, melt extrusion and calendering: melt-extrude the dried particles through an extruder, add a cross-linking agent and mix well, then spread them into a multi-layer film blowing machine and calender them into a film, cool them under natural conditions after film formation, and perform corona treatment;

[0016] Step 6: Pelletizing: The corona treated film is cut into tapes of desired shape and size by a pelletizer;

[0017] Step 7: Post-processing: coating and printing the tape surface.

[0018] Preferably, the mixing setting conditions in step 2 are: the temperature is controlled at 36-42° C., and the mixing time is controlled at 16-20 min.

[0019] Preferably, when the mixing in step 2 is carried out to 2 / 3 of the total set time, the amide dispersion, the alcohol dispersion and triallyl isocyanurate are added in a weight ratio of 3:1:2.

[0020] Preferably, the extrusion conditions of step three are: the temperature is controlled at 220-230° C., the pressure is controlled at 1.5-3.0 MPa, and the particle size is controlled between 1.5-2.5 μm.

[0021] Preferably, triallyl isocyanurate is added during the melt extrusion process in step five.

[0022] Preferably, the corona treatment in step five is performed for 3-5 minutes during the cooling and forming process of the film.

[0023] Compared with the prior art, the present invention provides a polyvinyl chloride electrostatic film tape, which has the following beneficial effects:

[0024] 1. The present invention can improve the comprehensive performance of the tape by selecting raw materials and adjusting the specific gravity range. Among them, the use of perchlorethylene resin can improve the antistatic performance of the tape, because it is not easy to burn and has stable chemical properties, which helps to reduce the generation and accumulation of static electricity, and nano-scale fly ash can reduce the adsorption between heavy metal particles on the surface of fly ash and fly ash, thereby improving the peel strength. The addition of carbon fiber can improve the adhesion performance of the tape, thereby increasing the peel strength, because the normal adhesion of carbon fiber composite materials on the silicon nitride surface is the highest. Betaine surfactants have good antistatic properties, washing foaming properties, thickening properties, hard water resistance, low irritation, conditioning properties, antibacterial properties and biodegradability. It is an amphoteric surfactant that can reduce the accumulation of static electricity. The above characteristics combined make the tape of the present invention perform well in antistatic performance and peel strength, and can be suitable for application scenarios requiring high antistatic performance and strong adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] See also Figure 1A polyvinyl chloride electrostatic film tape, the raw materials of the tape and their specific gravity range are: polyvinyl chloride 40% to 45%; perchloroethylene resin 11% to 14%; nano-level fly ash 12% to 16%; alkylamide phosphate betaine 2% to 5%; hydroxysulfonpropyl betaine 4% to 7%; carbon fiber 5% to 7%; aluminum dihydrogen phosphate 4% to 8%; lithium cyclohexane acid 3% to 6%; triallyl isocyanurate 1.52% to 1.94%.

[0028] Perchloroethylene resin: Perchloroethylene resin can improve the anti-static performance of the tape because it is non-flammable and chemically stable, which helps reduce the generation and accumulation of static electricity.

[0029] Nano-scale fly ash: Nano-scale fly ash can reduce the adsorption between heavy metal particles on the fly ash surface and the fly ash, thereby improving the peeling strength.

[0030] Carbon fiber: The adhesion performance of carbon fiber is affected by many physical properties such as the contact angle and roughness of the substrate. Among them, the normal adhesion of carbon fiber composite materials on the silicon nitride surface is the highest. Therefore, the addition of carbon fiber can improve the adhesion performance of the tape and thus increase the peel strength.

[0031] Betaine: Betaine surfactants have good antistatic properties, washing foaming properties, thickening properties, hard water resistance, low irritation, conditioning properties, antibacterial properties and biodegradability. Betaine is an amphoteric surfactant that can reduce the accumulation of static electricity.

[0032] Specifically, a polyvinyl chloride electrostatic film tape comprises the following steps:

[0033] Step 1, raw material preparation: weigh the raw materials in the formula ratio, including polyvinyl chloride, perchlorethylene resin, nano-scale fly ash, alkylamide phosphate betaine, hydroxysulfonpropyl betaine, carbon fiber, aluminum dihydrogen phosphate, lithium naphthenate and triallyl isocyanurate;

[0034] Step 2, mixing process: add the weighed raw materials into a high-speed mixer and mix (this step is to ensure that all ingredients are evenly distributed in the final product, thereby ensuring the performance consistency and reliability of the tape);

[0035] Step 3: Extrusion granulation: The uniformly mixed raw materials are fed into a twin-screw extruder for extrusion granulation (during the extrusion process, the temperature and pressure need to be strictly controlled to ensure that the material can be fully plasticized and form uniform particles);

[0036] Step 4: Drying: The extruded particles are placed in an oven for drying (to remove moisture and other volatile substances, which can improve the durability and stability of the tape);

[0037] Step 5, melt extrusion and calendering: melt-extrude the dried particles through an extruder, add a cross-linking agent and mix well, then spread them into a multi-layer film blowing machine and calender them into a film, cool them under natural conditions after film formation, and perform corona treatment (in the process of the multi-layer film blowing machine and the casting machine, the product is made in one time, which can improve production efficiency and product quality);

[0038] Step 6: Pelletizing: The corona treated film is cut into tapes of the required shape and size by a pelletizer (precise control to ensure the dimensional accuracy and surface quality of the tape);

[0039] Step 7: Post-processing: coating and printing the tape surface (to enhance its specific application performance).

[0040] Specifically, the setting conditions for mixing in step 2 are: the temperature is controlled at 36-42° C., and the mixing time is controlled at 16-20 min.

[0041] Specifically, when the mixing in step 2 is carried out to 2 / 3 of the total set time, an amide dispersion, an alcohol dispersion and triallyl isocyanurate are added in a weight ratio of 3:1:2 (to improve the dispersibility of the filler particles in the polymer and improve the stability and antistatic properties of the finished product).

[0042] Specifically, the extrusion conditions of step three are: the temperature is controlled at 220-230° C., the pressure is controlled at 1.5-3.0 MPa, and the particle size is controlled between 1.5-2.5 microns.

[0043] Specifically, triallyl isocyanurate is added during the melt extrusion process in step five (to increase the cross-linking degree of the material, thereby improving its heat resistance and mechanical properties).

[0044] Specifically, step five is corona treatment: corona treatment is performed for 3-5 minutes during the cooling and forming process of the film (so that the surface of the film is charged with static electricity during post-treatment to meet the needs of glue coating, which is beneficial to the combination of glue and film. The corona treatment does not increase the overall electrostatic function of the tape).

[0045] Example 1

[0046] The raw materials of the adhesive tape and their specific gravity are: 40% polyvinyl chloride; 14% perchlorethylene resin; 12% nano-level fly ash; 3% alkylamide phosphate betaine; 5% hydroxysulfonpropyl betaine; 6% carbon fiber; 7% dihydrogen aluminum phosphate; 5% lithium cyclohexane acid; and 1.60% triallyl isocyanurate.

[0047] Example 2

[0048] The raw materials and their proportions of the tape are: polyvinyl chloride 42%; perchloroethylene resin 13%; nano-level fly ash 12%; alkylamide phosphate betaine 2.4%; hydroxysulfonpropyl betaine 5%; carbon fiber 5.7%; dihydrogen aluminum phosphate 4.8%; lithium cyclohexane acid 5.2%; triallyl isocyanurate 1.52%.

[0049] Example 3

[0050] The raw materials and their proportions of the tape are: polyvinyl chloride 44%; perchloroethylene resin 14%; nano-level fly ash 13%; alkylamide phosphate betaine 2.5%; hydroxysulfonpropyl betaine 7%; carbon fiber 6%; dihydrogen aluminum phosphate 8%; lithium cyclohexaneate 6%; triallyl isocyanurate 1.94%.

[0051] Example 4

[0052] The raw materials of the tape and their specific gravity range are: polyvinyl chloride 40%; perchloroethylene resin 11%; nano-level fly ash 12.3%; alkylamide phosphate betaine 2.23%; hydroxysulfonpropyl betaine 6.99%; carbon fiber 6.77%; dialuminum phosphate 4.1%; lithium cyclopentaneate 3.3%; triallyl isocyanurate 1.62%.

[0053] Example 5

[0054] The raw materials of the tape and their specific gravity range are: polyvinyl chloride 42.5%; perchloroethylene resin 11.4%; nano-level fly ash 12.6%; alkylamide phosphate betaine 3.5%; hydroxysulfonpropyl betaine 5.67%; carbon fiber 6.37%; aluminum dihydrogen phosphate 4.5%; lithium cyclohexane acid 3.8%; triallyl isocyanurate 1.65%.

[0055] Example 6

[0056] The raw materials of the tape and their specific gravity range are: polyvinyl chloride 42%; perchloroethylene resin 11.9%; nano-level fly ash 14.6%; alkylamide phosphate betaine 4.55%; hydroxysulfonpropyl betaine 4.67%; carbon fiber 6%; dihydrogen aluminum phosphate 5%; lithium cyclohexaneate 3.9%; triallyl isocyanurate 1.74%.

[0057] Comparative Example 1

[0058] The raw materials of the adhesive tape and their specific gravity are: 40% polyvinyl chloride; 12% nano-level fly ash; 3% alkylamide phosphate betaine; 5% hydroxysulfonpropyl betaine; 6% carbon fiber; 7% aluminum dihydrogen phosphate; 5% lithium cyclohexane acid; 1.60% triallyl isocyanurate (based on Example 1, 14% perchlorethylene resin is deleted and 14% polyvinyl chloride is added).

[0059] Comparative Example 2

[0060] The raw materials of the adhesive tape and their specific gravity are: 42% polyvinyl chloride; 13% polypropylene resin; 12% nano-fly ash; 2.4% alkylamide phosphate betaine; 5% hydroxysulfonpropyl betaine; 5.7% carbon fiber; 4.8% aluminum dihydrogen phosphate; 5.2% lithium cyclohexane acid; 1.52% triallyl isocyanurate (based on Example 2, the perchlorethylene resin is replaced by polypropylene resin, and the weight ratio remains unchanged).

[0061] Comparative Example 3

[0062] The raw materials of the adhesive tape and their specific gravity are: 44% polyvinyl chloride; 14% perchlorethylene resin; 13% fly ash of conventional particle size; 2.5% alkylamide phosphate betaine; 7% hydroxysulfonpropyl betaine; 6% carbon fiber; 8% aluminum dihydrogen phosphate; 6% lithium cyclohexaneate; 1.94% triallyl isocyanurate (based on Example 3, the nano-grade fly ash is replaced with fly ash of conventional particle size, and the weight ratio remains unchanged).

[0063] Comparative Example 4

[0064] The raw materials of the adhesive tape and their specific gravity range are: 40% polyvinyl chloride; 11% perchlorethylene resin; 12.3% nano-level fly ash; 9.99% hydroxysulfonpropyl betaine; 6.77% carbon fiber; 4.1% aluminum dihydrogen phosphate; 3.3% lithium cyclohexane acid; 1.62% triallyl isocyanurate (based on Example 4, 2.23% of alkylamide phosphate betaine is deleted and 3% of hydroxysulfonpropyl betaine is added).

[0065] Comparative Example 5

[0066] The raw materials of the adhesive tape and their specific gravity range are: 42.5% polyvinyl chloride; 11.4% perchloroethylene resin; 12.6% nano-level fly ash; 3.5% alkylamide phosphate betaine; 5.67% hydroxysulfonpropyl betaine; 4.5% aluminum dihydrogen phosphate; 3.8% lithium cyclohexaneate; 1.65% triallyl isocyanurate (6.37% carbon fiber is deleted on the basis of Example 5).

[0067] Comparative Example 6

[0068] The raw materials of the adhesive tape and their specific gravity range are: 42% polyvinyl chloride; 11.9% perchlorethylene resin; 14.6% nano-level fly ash; 6% to 8% sulfopropyl betaine; 6% carbon fiber; 5% aluminum dihydrogen phosphate; 3.9% lithium cyclohexane acid; 1.74% triallyl isocyanurate (based on Example 6, 4.55% of alkylamide phosphate betaine and 4.67% of hydroxysulfopropyl betaine are replaced with 6% to 8% of sulfopropyl betaine).

[0069] The raw materials of the formulas of the embodiment and the comparative example were made into adhesive tapes, and various properties (peeling degree and antistatic effect and other properties, test methods, results and units) were tested. The performance test data are shown in the following table:

[0070]

[0071] Note:

[0072] Peel strength test: used to determine the maximum load that the tape can withstand during the peeling process. By applying a certain tensile force and measuring its changes, the tensile strength and toughness of the tape are evaluated.

[0073] Elongation test: Measures the deformation ability of the tape during stretching. By calculating the change in length before and after stretching, the elasticity and flexibility of the tape are evaluated.

[0074] Heat resistance test: including heat resistance, low temperature flexibility and anti-aging performance, etc. By simulating different environmental conditions, the performance stability of the tape in long-term use is tested.

[0075] Antistatic Effect: The antistatic performance of the tape is evaluated by measuring the static half-life, which is the time required for the static voltage to decay to half of its initial value.

[0076] Tensile strength test: used to determine the maximum load that the tape can withstand during stretching. By applying a certain tensile force and measuring its changes, the tensile strength and toughness of the tape are evaluated.

[0077] Adhesion performance test: evaluates the adhesion performance of the tape on different surfaces, usually expressed in the form of shear adhesion in Newtons per square centimeter (N / cm 2 ).

[0078] Thermal stability: Accelerated aging tests are used to evaluate the performance retention of the tape under high temperature conditions, usually expressed as the strength retention rate after aging, in percentage (%).

[0079] The following information can be obtained from the above table:

[0080] By comparing the raw material formulations of the adhesive tapes of the embodiments and comparative examples, the following information can be obtained:

[0081] Effect of perchlorethylene resin: Comparison of Example 1 with Comparative Example 1 shows that the addition of perchlorethylene resin (14%) can improve the peel strength of the tape, but reduce the elongation, heat resistance, antistatic effect, tensile strength, adhesion performance and thermal stability.

[0082] Comparison between polypropylene resin and perchlorethylene resin: Comparison between Example 2 and Comparative Example 2 shows that replacing perchlorethylene resin (13%) with polypropylene resin in Comparative Example 2 reduces peel strength and has an adverse effect on other properties.

[0083] Comparison of nano-scale fly ash and conventional particle size fly ash: Comparison of Example 3 with Comparative Example 3 shows that the use of nano-scale fly ash (13%) instead of conventional particle size fly ash in Example 3 can improve peel strength, elongation, heat resistance, antistatic effect, tensile strength, adhesion performance and thermal stability.

[0084] Effect of betaine type and ratio: Comparison of Example 4 with Comparative Example 4 shows that adjusting the ratio of alkylamide phosphate betaine and hydroxysulfonpropyl betaine can make the tape have an antistatic effect; among which, comparison of Example 6 with Comparative Example 6 shows that replacing other types of betaine with sulfonpropyl betaine will reduce the peel strength.

[0085] Effect of carbon fiber: Comparison of Example 5 with Comparative Example 5 shows that the addition of carbon fiber can improve the peel strength, elongation, heat resistance, antistatic effect, tensile strength, adhesion performance and thermal stability of the tape.

[0086] Effect of aluminum dihydrogen phosphate and lithium naphthenate: Comparison of the examples with the comparative examples shows that the addition of aluminum dihydrogen phosphate and lithium naphthenate helps to improve the heat resistance and thermal stability of the adhesive tape.

[0087] Effect of triallyl isocyanurate: Triallyl isocyanurate is used as a crosslinking agent, and the adjustment of its proportion will affect the mechanical properties and adhesion properties of the tape.

[0088] In summary, the performance of the tapes of the embodiments is generally better than that of the comparative examples, which indicates that the selection of raw materials and the specific gravity adjustment range of the present invention can improve the comprehensive performance of the tapes. Among them, the selection of types and proportions of perchlorethylene resin, nano-fly ash, carbon fiber and betaine can improve the antistatic performance of the tapes and increase the peel strength.

[0089] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A polyvinyl chloride electrostatic film tape, characterized in that: The raw materials of the adhesive tape and their specific gravity range are: 40% to 45% polyvinyl chloride; 11% to 14% perchloroethylene resin; 12% to 16% nano-level fly ash; 2% to 5% alkylamide phosphate betaine; 4% to 7% hydroxysulfonpropyl betaine; 5% to 7% carbon fiber; 4% to 8% aluminum dihydrogen phosphate; 3% to 6% lithium cyclohexane acid; and 1.52% to 1.94% triallyl isocyanurate.

2. The polyvinyl chloride electrostatic film tape according to claim 1, characterized in that: The raw materials of the adhesive tape and their specific gravity are: 40% polyvinyl chloride; 14% perchlorethylene resin; 12% nano-level fly ash; 3% alkylamide phosphate betaine; 5% hydroxysulfonpropyl betaine; 6% carbon fiber; 7% aluminum dihydrogen phosphate; 5% lithium cyclohexane acid; and 1.60% triallyl isocyanurate.

3. The polyvinyl chloride electrostatic film tape according to claim 1, characterized in that: The raw materials of the adhesive tape and their specific gravity are: 42% polyvinyl chloride; 13% perchlorethylene resin; 12% nano-level fly ash; 2.4% alkylamide phosphate betaine; 5% hydroxysulfonpropyl betaine; 5.7% carbon fiber; 4.8% aluminum dihydrogen phosphate; 5.2% lithium cyclohexane acid; and 1.52% triallyl isocyanurate.

4. The polyvinyl chloride electrostatic film tape according to claim 1, characterized in that: The raw materials of the adhesive tape and their specific gravity are: 44% polyvinyl chloride; 14% perchlorethylene resin; 13% nano-level fly ash; 2.5% alkylamide phosphate betaine; 7% hydroxysulfonpropyl betaine; 6% carbon fiber; 8% aluminum dihydrogen phosphate; 6% lithium cyclohexaneate; and 1.94% triallyl isocyanurate.

5. The polyvinyl chloride electrostatic film tape according to claim 1, characterized in that: The following steps are involved: Step 1, raw material preparation: weigh the raw materials in the formula ratio, including polyvinyl chloride, perchlorethylene resin, nano-scale fly ash, alkylamide phosphate betaine, hydroxysulfonpropyl betaine, carbon fiber, aluminum dihydrogen phosphate, lithium naphthenate and triallyl isocyanurate; Step 2, mixing process: adding the weighed raw materials into a high-speed mixer and mixing; Step 3: Extrusion granulation: feeding the uniformly mixed raw materials into a twin-screw extruder for extrusion granulation; Step 4: Drying: The extruded particles are placed in an oven for drying; Step 5, melt extrusion and calendering: melt-extrude the dried particles through an extruder, add a cross-linking agent and mix well, then spread them into a multi-layer film blowing machine and calender them into a film, cool them under natural conditions after film formation, and perform corona treatment; Step 6: Pelletizing: The corona treated film is cut into tapes of desired shape and size by a pelletizer; Step 7: Post-processing: coating and printing the tape surface.

6. The polyvinyl chloride electrostatic film tape according to claim 1, characterized in that: The setting conditions for mixing in step 2 are: the temperature is controlled at 36-42° C., and the mixing time is controlled at 16-20 min.

7. The polyvinyl chloride electrostatic film tape according to claim 6, characterized in that: When the mixing in the step 2 is carried out to 2 / 3 of the total set time, the amide dispersion, the alcohol dispersion and triallyl isocyanurate are added in a weight ratio of 3:1:

2.

8. The polyvinyl chloride electrostatic film tape according to claim 1, characterized in that: The extrusion conditions of step three are: the temperature is controlled at 220-230° C., the pressure is controlled at 1.5-3.0 MPa, and the particle size is controlled between 1.5-2.5 μm.

9. The polyvinyl chloride electrostatic film tape according to claim 1, characterized in that: In the step 5, triallyl isocyanurate is added during the melt extrusion process.

10. The polyvinyl chloride electrostatic film tape according to claim 1, characterized in that: The step 5 of corona treatment is to perform corona treatment for 3-5 minutes during the cooling and forming process of the film.

Citation Information

Patent Citations

  • Polyvinyl chloride insulating antistatic membrane and preparation method thereof

    CN106519487A

  • Polyvinyl chloride insulation film for battery packaging and preparation method thereof

    CN106543586A

  • Insulating film for battery packaging and manufacturing method of insulating film

    CN106566118A

  • Adhesive film or tape

    JP1996012949A

  • Method for improving adhesion between adhesives and polyester or other thermoplastic substrates

    US3962498A